Angela's Ashes - Copyright Collection (Library of Congress) (1999)
Based on the best selling autobiography by Irish expat Frank McCourt, Angela's Ashes follows the experiences of young Frankie and his family as the try against all odds to escape the poverty endemic in the slums of pre-war Limerick. he film opens with the family in Brooklyn, but following the death of one of Frankie's siblings, they return home, only to find the situation there even worse. Prejudice against Frankie's Northern Irsh father makes his search for employment in the Republic difficult despite his having fought for the IRA, and when he does find money, he spends the money on drink.
Copyright: Paramount Pictures Corporation & PolyGram Holding, Inc. (employer for hire). Prev. reg.: Some musical compositions prev. pub.; screenplay prev. reg. NM: motion picture excluding prev. reg. musical compsotions. DCR 1999; PUB 22Dec99; REG 9Feb00; PA968-094.
Summary taken from Internet database.
Digital sound on two compact discs stored in one film can (CGC 9574).
Sources used: copyright data base; copyright data sheet.
Emily Watson, Robert Carlyle, Joe Breen, Ciaran Owens, Michael Legge.
Keywords: Drama -- Feature